1992
DOI: 10.1063/1.462737
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced shifts of CO2 lines: Measurements in the 003–000 band and theoretical analysis

Abstract: Self-broadened and N2, Ar, He-broadened halfwidth and pressure shift coefficients of the rotational transitions in the 0003–0000 band of 12C16O2 have been measured from laboratory absorption recorded at room temperature with a Fourier transform spectrometer. Comparison is made with the results of a theoretical calculation based on a semiclassical model. Good agreement is obtained for all the IR vibrational bands for which data are available. It has been shown that the shifts mainly originate from vibrational d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 22 publications
6
45
0
Order By: Relevance
“…This mandated the use of low gas pressures since previous studies [48][49][50][51][52][53][54][55] showed that CO 2 transitions in the NIR experience large, negative pressure-induced frequency shifts with strong dependencies on J and DJ . Ideally, line positions should be acquired from spectra with pressures of 2 Torr or less.…”
Section: Methodsmentioning
confidence: 99%
“…This mandated the use of low gas pressures since previous studies [48][49][50][51][52][53][54][55] showed that CO 2 transitions in the NIR experience large, negative pressure-induced frequency shifts with strong dependencies on J and DJ . Ideally, line positions should be acquired from spectra with pressures of 2 Torr or less.…”
Section: Methodsmentioning
confidence: 99%
“…where • S iso 1 is a vibrational phase shift defined from the difference of the isotropic part of the potential in the initial and final states of transition [24]: S iso 1 ¼ S 1;f2 À S 1;i2 ; • the real part of S aniso 2 derived from the anisotropic part of the potential is expressed as the second-order terms of the development of…”
Section: Theoretical Calculations Of Shiftsmentioning
confidence: 99%
“…at 300 K. The linewidths are plotted as a function of the rotational quantum number m modulus (m D J for P-branch and m D J C 1 for R-branch) in order to permit a comparison with experimental data 21,22 mainly obtained for P-branches.…”
Section: Co 2 -He Systemmentioning
confidence: 99%